2017
DOI: 10.1111/1365-2656.12757
|View full text |Cite
|
Sign up to set email alerts
|

Fast‐growing oysters show reduced capacity to provide a thermal refuge to intertidal biodiversity at high temperatures

Abstract: Ecosystem engineers that modify the thermal environment experienced by associated organisms might assist in the climate change adaptation of species. This depends on the ability of ecosystem engineers to persist and continue to ameliorate thermal stress under changing climatic conditions-traits that may display significant intraspecific variation. In the physically stressful intertidal, the complex three-dimensional structure of oysters provides shading and traps moisture during aerial exposure at low tide. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 47 publications
1
39
0
Order By: Relevance
“…Heat stress on rocky shores generally increases with the amount of primary substrata exposed to the sun (Lathlean, ). In a previous field study manipulating the density of horizontally orientated oysters, we found that substrate temperature increased as oyster cover decreased (McAfee et al, ). In the present mesocosm experiment, however, vertically orientated oysters caused cooler tile temperatures than horizontally orientated oysters, despite their occupation of a smaller amount of tile space (an experimental artefact of standardizing oyster biomass).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Heat stress on rocky shores generally increases with the amount of primary substrata exposed to the sun (Lathlean, ). In a previous field study manipulating the density of horizontally orientated oysters, we found that substrate temperature increased as oyster cover decreased (McAfee et al, ). In the present mesocosm experiment, however, vertically orientated oysters caused cooler tile temperatures than horizontally orientated oysters, despite their occupation of a smaller amount of tile space (an experimental artefact of standardizing oyster biomass).…”
Section: Discussionmentioning
confidence: 78%
“…Where efforts to restore ecosystem engineers do not achieve the structural traits critical to environmental amelioration, the desired ecological outcomes may not be achieved (Irving & Bertness, ). In the present case, oysters can provide refugia for intertidal biodiversity from environmental extremes (McAfee et al, ), but this is dependent on the structural traits of the oyster beds and, in order for this function to be maximized, vertically structured configurations are most effective. Hence, in order to maximize the benefits of oyster reef restoration projects in providing climate refugia to associated biodiversity, vertical growth forms should be encouraged through restoration methodologies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…subtidal habitats), the complex structure of S. glomerata provides refugia from predators (McAfee & Bishop ). In dampening the impacts of climate and biotic stress, the restoration of S. glomerata reefs can be considered a climate adaption strategy, providing associated organisms more time to adapt to the changing environment (McAfee ).…”
Section: Benefits Of Sydney Rock Oyster Reef Restorationmentioning
confidence: 99%